EASY SKIP - Gabriel Fernandes Vargas, Alex; Fernandes da Silva, Brendon; Augusto Magalhães dos Santos, Cà©sar; Nepomuceno Ribeiro Silva, Erick; Francisco, Gabriel; de Sousa Andrade, Kevin; Santos Faria Silva, Talles (CIPEEX, 2024)
EASYSKIP IS A MULTI-PURPOSE SOFTWARE SOLUTION THAT WAS CREATED TO HELP PEOPLE WITH THEIR ORDERS AND WORK ROUTINE. IT HAS NEVER BEEN EASIER TO REQUEST THE DELIVERY OF A PRODUCT OR CARRY OUT LOGISTICAL SERVICES WITH A FINANCIAL RETURN. IN ADDITION, EASYSKIP IS A PLATFORM DEVELOPED TO MEET THE NEEDS OF A LARGE NUMBER OF PEOPLE WHO NEED DELIVERY SERVICES, SO THAT IT IS POSSIBLE TO REGISTER USERS FROM DIFFERENT SECTORS, WHETHER IN THE GENERAL OR FOOD INDUSTRY, ETC. IN THIS WAY, THE APPLICATION BECOMES A USEFUL WORKING TOOL FOR SMALL AND LARGE BRANDS. INITIALLY, THE PLATFORM WILL OPERATE THROUGH WEB BROWSERS AND CAN LATER BE IMPLEMENTED IN OTHER MEDIA SUCH AS MOBILE AND DESKTOP ENVIRONMENTS. ONE OF THE MOST INTERESTING FEATURES OF EASYSKIP IS ITS ABILITY TO CUSTOMIZE DELIVERY PREFERENCES, ALLOWING USERS TO CONFIGURE OPTIONS THAT PERFECTLY MEET THEIR PERSONAL NEEDS. WHETHER IT’S CHOOSING SPECIFIC DELIVERY TIMES, SELECTING FAVORITE PAYMENT METHODS OR MAKING OTHER PERSONALIZED SETTINGS, EASYSKIP OFFERS THE FLEXIBILITY TO ADAPT TO A VARIETY OF PREFERENCES. IN SHORT, THE PLATFORM OFFERS A DYNAMIC DELIVERY SERVICE, WITH A FOCUS ON SIMPLIFYING THE PROCESS OF REQUESTING DELIVERIES, MAKING IT MORE PRACTICAL AND EFFICIENT. USERS CAN EASILY ORDER PRODUCTS OR SERVICES THROUGH THE PLATFORM, ELIMINATING MANY OF THE PROBLEMS AND INCONVENIENCES COMMON TO CONVENTIONAL LOGISTICS METHODS. THIS NOT ONLY SAVES TIME, BUT CAN ALSO CONSIDERABLY IMPROVE THE OVERALL EFFECTIVENESS OF DELIVERY OPERATIONS. IN ADDITION TO ITS ADVANTAGES FOR COMPANIES AND BRANDS, EASYSKIP AIMS TO HELP THE DAY-TO-DAY LIVES OF INDIVIDUAL USERS, OFFERING CONVENIENCE AND EASE IN REQUESTING DELIVERIES OF OBJECTS, GROCERIES, MEALS OR ANY OTHER PRODUCT, SAVING TIME AND EFFORT. BY CUSTOMIZING DELIVERY PREFERENCES, USERS CAN DEFINE HOW THEY WISH TO RECEIVE THEIR PRODUCTS, BRINGING PRACTICALITY AND EFFICIENCY TO OUR DAILY LIVES. IN SHORT, EASYSKIP IS AN INNOVATIVE SOLUTION THAT PROMISES TO CONSIDERABLY SIMPLIFY AND IMPROVE ORDER MANAGEMENT AND LOGISTICS OPERATIONS. ITS ADAPTABILITY MAKES IT A VALUABLE TOOL FOR COMPANIES OF ALL SIZES AND SECTORS, PROVIDING GREATER EFFICIENCY AND CONVENIENCE. WITH THE OPTION TO EXPAND TO OTHER DEVICES AND THE ABILITY TO CUSTOMIZE DELIVERY PREFERENCES, EASYSKIP IS WELL PLACED TO SHAPE THE FUTURE OF LOGISTICS SERVICES, MAKING THEM MORE EFFECTIVE AND ACCESSIBLE TO A WIDER AUDIENCE. THIS PLATFORM HAS THE POTENTIAL TO REVOLUTIONIZE HOW COMPANIES MANAGE THEIR DELIVERY OPERATIONS, MAKING THEM MORE EFFICIENT AND SATISFYING FOR THEIR CUSTOMERS.